2007
DOI: 10.1007/s12088-007-0046-2
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of an indigenous ELISA for diagnosis of Johne’s disease and its comparison with commercial kits

Abstract: Country lacks sensitive and indigenous diagnostic kits for the screening of goats and sheep against Johne's disease. Therefore an indigenous ELISA kit was developed using protoplasmic antigen from native Mycobacterium avium subspecies paratuberculosis 'Bison Type' strain of goat origin (Kit 1). In the present study, kit 1 and two commercial kits (kit 2 and 3) were evaluated with respect to 'Gold Standard' fecal culture in 71 animals (55 goats and 16 sheep). Kit 1 using indigenous antigen (protoplasmic antigen)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 14 publications
3
31
0
1
Order By: Relevance
“…Using 3 antigens from geographically distinct regions of the world showed that it was prudent to use species specific antigen prepared from native strain (S 5) of MAP, the novel dominant bio-type ('Indian Bison Type') reported first time in the world from India (Sohal et al, 2009;Singh et al, 2013a). Similar findings have been reported in our earlier studies (Singh et al, 2007b). Present study also used semi-purified protoplasmic antigen from strain 'S 5' of MAP of goat origin in 'Indigenous g-ELISA' which detected highest percentage (90.0%) of sheep as positive and sheep was positive independently in the test.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Using 3 antigens from geographically distinct regions of the world showed that it was prudent to use species specific antigen prepared from native strain (S 5) of MAP, the novel dominant bio-type ('Indian Bison Type') reported first time in the world from India (Sohal et al, 2009;Singh et al, 2013a). Similar findings have been reported in our earlier studies (Singh et al, 2007b). Present study also used semi-purified protoplasmic antigen from strain 'S 5' of MAP of goat origin in 'Indigenous g-ELISA' which detected highest percentage (90.0%) of sheep as positive and sheep was positive independently in the test.…”
Section: Discussionsupporting
confidence: 90%
“…Sheep detected positive in 'Indigenous g-ELISA' were also detected by other tests in 2 and 3 tests combinations. Previous studies by Singh et al (2007b) using Purified Protoplasmic Antigen (PPA) from Allied Monitor Inc., USA exhibited poor cross reactivity with sheep sera. However, in the present study purified PPA of bovine origin from Allied Monitor Inc., USA (supplied by ID Vet, France) exhibited better sensitivity and detected 77.5% sheep positive.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations